BIODIESEL PRODUCTION USING HERMETIA ILLUCENS (BLACK SOLDIER FLY)PRE-PUPAE BIOMASS THROUGH ORGANIC WASTE UPCYCLING - YOONG, LEONG SIEW (2016)
This study investigates the bioconversion of H illucens for biodiesel production via transformation of organic waste (sewage sludge, fruit waste, oil palm decanter and food waste). These wastes were used as the feed for the larvae. The study was to evaluate the growth rate of the larvae through transformation of various organic wastes.